1995
DOI: 10.1016/0166-445x(95)00004-n
|View full text |Cite
|
Sign up to set email alerts
|

Integrated physiological response of tilapia, Oreochromis mossambicus, to sublethal copper exposure

Abstract: Juvenile and mature tilapia {O reochrom is m ossam bicus) were exposed to a range o f sublethal copper (Cu) concentrations for 6 days to examine the mechanisms underlying the acclimation to the toxic effects o f the metal. The study focuses on the gills, the primary target for waterborne pollutants. To obtain a comprehensive picture o f the branchial acclimation processes operating, multiple biochemical and m orphological parameters were studied. A t all concentrations tested, Cu exposure resulted in the accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 46 publications
6
87
0
1
Order By: Relevance
“…Copper concentrations as low as 20 µg L -1 decreased the concentration of sodium in the plasma and at a concentration of 29 µg L -1 (96 h LC 50 (Mazon & Fernandes, 1999)), plasma sodium and chloride were significantly lower than the control, with a concomitant increase in plasmatic potassium concentration. Previous investigations have also found ion imbalance in Salvelinius fontinalis (McKim et al, 1970), Ictalurus nebulosus (Christensen et al, 1972), Lepomis macrochirus (Heath, 1991), and O. mossambicus (Nussey et al, 1995a;Pelgrom et al, 1995). Ionregulatory disruption induced by copper is related to inhibition of branchial Na + -K + -ATPase and ion uptake with concomitant stimulation of ion efflux in freshwater fish (Laurén & McDonald, 1985;Pelgrom et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Copper concentrations as low as 20 µg L -1 decreased the concentration of sodium in the plasma and at a concentration of 29 µg L -1 (96 h LC 50 (Mazon & Fernandes, 1999)), plasma sodium and chloride were significantly lower than the control, with a concomitant increase in plasmatic potassium concentration. Previous investigations have also found ion imbalance in Salvelinius fontinalis (McKim et al, 1970), Ictalurus nebulosus (Christensen et al, 1972), Lepomis macrochirus (Heath, 1991), and O. mossambicus (Nussey et al, 1995a;Pelgrom et al, 1995). Ionregulatory disruption induced by copper is related to inhibition of branchial Na + -K + -ATPase and ion uptake with concomitant stimulation of ion efflux in freshwater fish (Laurén & McDonald, 1985;Pelgrom et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Metal-metal interactions after single metal exposure were shown by Gill et al (1992) who reported an increased Cu concentration in the gills of eels after Cd exposure. Previous experiments with single metal exposed fish have shown effects of sublethal concentrations of Cu or Cd on the number and function of ion transporting cells in the gills (Baker, 1969;Verbost et al, 1987;Reid and McDonald, 1988;Pratap and Wendelaar Bonga, 1993;Pelgrom et al, 1995). Exposure to low Cd concentrations resulted in an unexpectedly high increase in metal concentration in the gills.…”
Section: Gillsmentioning
confidence: 91%
“…The branchial damage can include: a reduction in Na + influx McDonald, 1985, 1987a) a stimulation of Na + efflux (Laurén and McDonald, 1985) and an inhibition of branchial Na + -K + ATPase activity (Stagg and Shuttleworth, 1982;Laurén and McDonald, 1987b;Pelgrom et al, 1995;Kolok et al, 2002). These branchial changes can lead to an increase in net Na + loss (Croke and McDonald, 2002;Taylor et al, 2004), which can culminate in a significantly reduced concentration of whole-body Na + (Laurén and McDonald, 1987a;McGeer et al, 2000;Kolok et al, 2002).…”
Section: Introductionmentioning
confidence: 99%